Faculty Readiness on Computational Sustainability: A Literature Synthesis on the Readiness Dimensions - Tuan Rahim, Tuan NurNadzirah 'Asyikin; Ismail, Azniah; Ubaidullah, Nor Hasbiah; Fathil, Nur Saadah; Kamaruddin, Kamalia Azma; Zakaria@Mohamad, Aznida Hayati; Mohd Zulkefli, Nurul Akhmal (Journal of ICT in Education, 2024)
Computational sustainability has become a key topic bridging environmental science, computer science, and sustainability research. This literature review explores the readiness dimensions necessary for advancing computational sustainability projects and examines how computational tools are applied to address sustainability challenges across various domains. This study examines 33 case studies and 56 empirical research papers that demonstrate the use of computational tools to improve readiness in a variety of scenarios, including technology readiness, faculty readiness, teaching readiness, e-learning readiness, and green education. By extensively reviewing previous material, this synthesis identifies recurring themes and emerging trends in readiness assessment across many sustainability sectors, case studies, and empirical research. The study blends several views and approaches, resulting in a better understanding of how readiness aspects might aid in the application and efficacy of computational tools in sustainability research. The literature synthesis highlights the dimensions of readiness in this study, ranking technological knowledge (35%), content knowledge (25%), teaching strategies (20%), training (15%), and equipment/software (5%) based on their significance in determining how well societies are prepared to effectively adopt sustainable practices. This literature synthesis explores readiness factors in computational sustainability, highlighting recent advancements and trends. The review focused on English-language publications from 2018 to 2024, with additional research from 2010 to 2017. This comprehensive analysis of faculty readiness for computational sustainability aims to enhance its effectiveness, paving the way for broader studies that benefit researchers, faculties, students, policymakers, and society.